Prohibition of competition and non-compete clause - Senčur Peček, Darja (Anali PAZU HD, 2022)
For the duration of the employment relationship, an employee is obliged to refrain from all actions that could harm the employer. This is the so-called employee’s duty of loyalty to the employer. An expression of the employee’s duty of loyalty is also a prohibition of competitive activity. An employee is already forbidden by law to carry out an activity that could represent competition for the employer, without the the employer’s consent. This prohibition only applies for the duration of the employment relationship. In certain cases, an employer has a legitimate interest to prevent an employee from performing competitive activity even after the termination of the employment relationship. This mostly applies to employees who have during their work with the employer gained an insight into certain procedures or practices that are relevant to the competitive capacity of the company. In such cases, the employee and the employer may agree with the so-called competition clause in the employment contract that, for a certain period after the termination of the employment relationship, the employee will not perform competitive activity where he would benefit from the knowledge and business connections gained with the former employer. The article discusses currently valid regulation of the prohibition of competition and non-compete clause, analyses case law related to these institutions, highlights legal problems that arise in their application, and suggests possible solutions.